Rheumatoid Arthritis: Notable Biomarkers Linking to Chronic Systemic Conditions and Cancer - O. Olumuyiwa-Akeredolu, Oore-ofe; Pretorius, Etheresia (Current Pharmaceutical Design, 2016)
Adult rheumatoid arthritis (RA) is an autoimmune disorder affecting joints and frequently characterised by initial local and later systemic inflammation. Researchers have, for many years, traced its cause to diverse genetic, environmental and especially immunological responses that work against the body’s own cells and tissues. Investigation into several of these biomarkers reveals interconnections that exist between multiple factors, which ultimately lead to specific pathologies. The goal of this paper is to highlight connections present between the major biological players long identified by researchers including more recently uncovered biomarkers in the RA repertoire and some of the pathophysiologies typically affiliated with the disease. Biomarkers reviewed, and becoming more clearly defined for RA include genetic, cytokines like tumor-necrosis factor-α (TNF-α), lymphocytes, nuclear antigens, antibodies to citrullinated peptides (anti-CPs), acute-phase proteins (APPs), microRNA, S100 proteins, platelets and erythrocytes. Some of the disease manifestations that have been connected are bone erosion, diabetes, metabolic syndrome, anemia, synovitis, felty’s syndrome, extra-articular manifestations (EAMs) such as atherosclerosis, rheumatoid nodules and cardiovascular (CV) events. Several RA markers associated with malignancy have been identified in literature although there is insufficient evidence of cancer in patients. Due to the complex nature of the disease, the appearance of symptoms and markers vary amongst individuals and the connections may manifest only in part. This manuscript addresses defining factors relevant to rapid identification of pathological influences these biomolecules could exert and to the management of the disease. Each of these biological players may have its place in connecting to symptomatic pathologies and help to highlight potential targets for therapy.
Keywords: pathology